Pengujian Konstruk Kepuasan Mahasiswa yang Dikembangkan Oleh Lijuan Zhai (2012) Dalam Konteks Universitas Teuku Umar: Analisis Menggunakan Program SMARTPLS (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
This study aimed to examine the construct of student satisfaction developed by Lijuan Zhai (2012) in the context of Universitas Teuku Umar. The tests carried out include validity and reliability using the SmartPLS 3.2.9 program. The sample used was 371 respondents who were selected. The results showed that the relevant indicators of student satisfaction in the context of Universitas Teuku Umar were only five indicators covered in two dimensions, namely (a) curriculum and instruction, four indicators namely KM6, KM7, KM8, and KM9, and (b) counseling/advising, one indicator is KM18. Meanwhile, as many as 58 indicators are considered irrelevant because they do not meet the validity and reliability test requirements. Maybe this is understandable because there are differences in terms of needs, ethics, or culture.